Incidental Discovery of Giant Ovarian Cysts During Autopsy. Case Analysis and Literature Review - Kazlauskaitė, Justė; Chmieliauskas, Sigitas; Vasiljevaitė, Diana; Laima, Sigitas (Acta medica Lituanica, 2024)
Background: Cysts are called giant when they are >10 cm in diameter. Today the frequency of giant ovarian cysts is decreasing due to good diagnostic methods and regular gynecological examination. These cysts occur more frequently in women of reproductive and postmenopausal age. The most common giant cysts are benign serous cystadenomas. Diagnosing giant cysts can be hindered by nonspecific symptoms, the patient‘s reluctance to see a doctor and fear of surgery. The purpose of this study is to review the existing literature on this topic and describe three cases of giant cysts found at autopsy.Materials and methods: A literature review was conducted in the Medline (PubMed) database over a period of 10 years. The information concerning the examination of deceased individuals after their death was sourced from the database of the Lithuanian State Forensic Medicine Service. After the analysis of the deceased persons in the years 2015–2022 in the State Forensic Medicine Service, out of 1638 deceased persons, three cases of giant cysts were identified. These three cases were analyzed retrospectively.  During these investigations, the circumstances of finding the scene, the results of the autopsy, and the data of additional toxicological and microscopic tests were evaluated.Results: A retrospective study of 3 cases confirms the fact that giant ovarian cysts are a rare phenomenon. In case 1, the corpse of a 75-year-old woman was examined, a 30x30x25 cm left ovarian cyst was found, the woman had chronic ischemic heart disease; case 2 was a 65-year-old woman with a 19x25x12 cm right ovarian cyst and deep vein thrombosis with pulmonary embolism; case 3 was a 62-year-old woman with a 40x30x30 cm right ovarian cyst and chronic ischemic heart disease. In all cases, giant ovarian cysts were incidental findings and not the primary cause of death. The described clinical cases corresponded to the characteristics of giant cysts indicated in the literature: appeared in the postmenopausal period, benign course, diagnosed in patients who did not seek medical attention.Conclusions: Thanks to good early diagnosis, ovarian cysts are diagnosed early, before they reach gigantic size, so giant cysts are extremely rare. Delayed diagnosis is related to reluctance of patients to consult doctors and confusion with ascites and obesity. They are usually benign, and the symptoms they cause are related to mass effect – pressure on nearby organs.
Keywords: giant ovarian cyst; giant ovarian cystadenoma